Efficacy of administration of coagulation factor XIII with definitive surgery for multiple intractable enterocutaneous fistulae in a patient with decreased factor XIII activity. (15th March 2011) - Saigusa, Susumu; Yamamura, Takeshi; Tanaka, Koji; Ohi, Masaki; Kawamoto, Aya; Kobayashi, Minako; Inoue, Yasuhiro; Kusunoki, Masato
Abstract : Enterocutaneous fistulae (ECF) are challenging problem commonly encountered by surgeons and cause significant complications. They not only prolong hospital stay, but also restrict a patient's activities of daily living. The authors report a case of successful treatment of multiple intractable ECF in a patient with decreased coagulation factor XIII (FXIII) activity using intravenous FXIII treatment. A 74-year-old man with multiple ECF was referred. Although no factors involved in impaired wound were initially identified, he developed ECF after multiple surgical interventions with repeated wound dehiscence. FXIII activity was below the normal value. A definitive operation was performed and FXIII was administrated for 5 days postoperatively. There was no fistula recurrence and no other complications. Preoperative assessment of factors related to wound repair, such as FXIII activity, may be important for patients with wound dehiscence and subsequent fistula development and should be considered in patients who are resistant to standard treatments.